Incidental findings on chest CT imaging are associated with increased COPD exacerbations and mortality - Jairam, Pushpa M; van der Graaf, Yolanda; Lammers, Jan-Willem J; Mali, Willem P Th M; de Jong, Pim A (Thorax, 2015)
BackgroundThis study aimed to evaluate whether incidental CT findings of emphysema, airway thickening and bronchiectasis, as seen on CT scans performed for other non-pulmonary clinical indications, are associated with future acute exacerbations of COPD resulting in hospitalisation or death.MethodsThis multicentre prospective case–cohort study comprised 6406 subjects who underwent routine diagnostic chest CT for non-pulmonary indications. Using a case–cohort approach, we visually graded CT scans from cases and a random sample of ∼10% of the baseline cohort (n=704) for emphysema severity (range 0–20), airway thickening (range 0–5) and bronchiectasis (range 0–5). We used weighted Cox proportional hazards analysis to assess the independent association between CT findings and hospitalisation or death due to COPD exacerbation.ResultsDuring a median follow-up of 4.4 years (maximum 5.2 years), 338 COPD events were identified. The risk of experiencing a future acute exacerbation of COPD resulting in hospitalisation or death was significantly increased in subjects with severe emphysema (score ≥7) and severe airway thickening (score ≥3). The respective HRs were 4.6 (95% CI 3.0 to 7.1) and 5.9 (95% CI 3.4 to 10.5). Severe bronchiectasis (score ≥3) was not significantly associated with increased risk of adverse events (HR 1.5; 95% CI 0.9 to 2.5).ConclusionsMorphological correlates of COPD such as emphysema and airway thickening detected on CT scans obtained for other non-pulmonary indications are strong independent predictors of subsequent development of acute exacerbations of COPD resulting in hospitalisation or death.